A Rare Variation in Branching Pattern of the Internal Iliac Artery: A Case Report - Masoumeh Faghani Langroudi; Mehrdad Asgari Asgari; Mojgan Mesbah (Negah Institute for Scientific Communication, 2014)
Internal iliac artery (IIA) shows frequent variations in its branching pattern. We saw variations in the branching pattern of right IIA in a male cadaver. The IIA divided into anterior and posterior divisions. The branches of the anterior division included umbilical artery, inferior vesical artery, obturator artery. The other branches arose from posterior trunk such as iliolumbar, lateral sacral, internal pudendal, superior and inferior gluteal arteries. Knowledge of these variations might be useful for the radiologists and surgeons.